Ancaman Keberlanjutan Koperasi Akibat Permasalahan Pakan pada Kelompok Peternak atau Koperasi Sapi Perah di Indonesia - Sulistyati, Marina; Saputra, Arif Ragil; Herlina, Linda; Yunasaf, Unang; Nurlina, Lilis; Alim, Syahirul; Mauludin, Mohamad Ali (Universitas Galuh, 2025)
Cooperatives and farmer groups in Indonesia's dairy sector are facing several serious challenges that can threaten their sustainability. One of the main issues is the availability and quality of livestock feed. This literature study aims to analyze and summarize various aspects of the threats to the sustainability of cooperatives and farmer groups caused by feed-related problems in the context of dairy cattle in Indonesia. The research method employed in this study is literature review. This literature study investigates issues related to livestock feed, such as inadequate feed availability, feed prices, and the quality of feed that can affect the productivity and health of dairy cattle. The results of the literature study indicate that uncertainty in feed supply, rising feed prices, and the lack of access to high-quality feed for farmers are the primary threats to the continued operation of cooperatives and farmer groups. Therefore, cooperatives must have a strategy to anticipate threats related to feed issues in order to maintain the sustainability of the cooperative.